Ravishment Twice Weekly: De Quincey's Opera Pleasures - O’Quinn, Daniel (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThe suddenly undecidable moment when one is both inside and outside oneself is De Quincey's recurring predicament, for whether he is on paper or on opium, there is a fundamental disappropriation which opens the intimate experience of opium onto the extimate experience of community. This essay examines the main contours of this disappropriation through an analysis of De Quincey’s deployment of musical figures and specifically the opera singer Josephina Grassini in his theorization of being-on-opium in Confessions of an English Opium-eater. Grassini’s public persona is as important as her inimitable voice to De Quincey’s explication of the effects of opium because she was quite famously Napolean’s lover. This amorous affiliation is a vital component in De Quincey’s account of opium experience because the erotic dynamics of Grassini’s performance allow us to specify the conflation of sexual and patriotic desire in De Quincey’s text. The apocalyptic form of British nationalism which is so vital to the coherence of the opium subject is inflected by a series of violent erotic fantasies crystallized around Grassini’s performances in the King’s Theatre. This essay contends that the nationalist gestures embedded in the invocation of Grassini can be elucidated by engaging with De Quincey's understanding of the relationship between tragedy, opera and community. This particular conjunction of theory and practice establishes a way of articulating the relationship between political and aesthetic experience that stays with De Quincey throughout his career. For example, his essay “Theory of Greek Tragedy.” which was published almost twenty years after the Confessions, underlines not only the analogy between tragedy and opera that animates his descriptions of the operatic scenes in the Confessions, but also the responsibility of both forms of theatre to the consolidation of the state. The ontological disturbance effected by opium is put in abeyance by an investment in sexualized phantasms of national identity that involve both a consolidation that is constantly on the verge of incoherence and a ruthless practice of othering.